Essentials of coating, painting, and lining for the oil, gas and petrochemical industries - Bahadori, Alireza (Amsterdam : GPP, an imprint of Elsevier, 2015)
With the oil and gas industry facing new challenges-deeper offshore installations, more unconventional oil and gas transporting through pipelines, and refinery equipment processing these opportunity feedstocks--new corrosion challenges are appearing, and the oil and gas industry's infrastructure is only as good as the quality of protection provided and maintained. Essentials of Coating, Painting, and Linings for the Oil, Gas, and Petrochemical Industries is the first guide of its kind to directly deliver the necessary information to prevent and control corrosion for the components on the offshore rig, pipelines underground and petrochemical equipment. Written as a companion to Cathodic Corrosion Protection Systems, this must-have training tool supplies the oil and gas engineer, inspector and manager with the full picture of corrosion prevention methods specifically catered for oil and gas services. Packed with real world case studies, critical qualifications, inspection criteria, suggested procedure tests, and application methods, Essentials of Coating, Painting, and Linings for the Oil, Gas and Petrochemical Industries is a required straightforward reference for any oil and gas engineer and manager.
1.21.2 -- Reagents Required.
Includes bibliographical references and index.
Online resource; title from PDF title page (Ebsco, viewed Jan. 15, 2015).
Elsevier
Keywords: Protective coatings; Surfaces (Technology); Coating processes; Petroleum industry and trade -- Equipment and supplies; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Coating processes; Petroleum industry and trade -- Equipment and supplies; Protective coatings; Surfaces (Technology); Electronic books; Electronic books